(untitled) (Oxford ; New York, 2009)
These volumes offer an opportunity to revisit the whole of international criminal law. It appraises the contribution made to international criminal law by post-World War II national criminal courts and tribunals, and it makes a critical assessment of the Rome Statute as a viable working tool for international criminal justice
Keywords: International criminal courts,Tòa án tội phạm quốc tế